Clinical on-site monitoring of ß-lactam antibiotics for a personalized antibiotherapy - Bruch, R.; Chatelle, C.; Kling, A.; Rebmann, B.; Wirth, S.; Schumann, S.; Weber, W.; Dincer, C.; Urban, G. (Scientific reports, 2017)
An appropriate antibiotherapy is crucial for the safety and recovery of patients. Depending on the clinical conditions of patients, the required dose to effectively eradicate an infection may vary. An inadequate dosing not only reduces the efficacy of the antibiotic, but also promotes the emergence of antimicrobial resistances. Therefore, a personalized therapy is of great interest for improved patients’ outcome and will reduce in long-term the prevalence of multidrug-resistances. In this context, on-site monitoring of the antibiotic blood concentration is fundamental to facilitate an individual adjustment of the antibiotherapy. Herein, we present a bioinspired approach for the bedside monitoring of free accessible ß-lactam antibiotics, including penicillins (piperacillin) and cephalosporins (cefuroxime and cefazolin) in untreated plasma samples. The introduced system combines a disposable microfluidic chip with a naturally occurring penicillin-binding protein, resulting in a high-performance platform, capable of gauging very low antibiotic concentrations (less than 6 ng ml −1 ) from only 1 µl of serum. The system’s applicability to a personalized antibiotherapy was successfully demonstrated by monitoring the pharmacokinetics of patients, treated with ß-lactam antibiotics, undergoing surgery.